Factors Affecting Efficiency of Performance Management System in Public Service Institutions - Fabianova, Zuzana (International Journal of Scientific Research and Management (IJSRM), 2016)
The performance management system has its specificities in public service institutions, which arise especially from the nature of the institution's work and from various interactions with interested parties. This paper focuses on the analysis of some factors that affect the efficiency of performance management systems in public service institutions to a various degree.  Results are based on a survey that verified hypotheses related to three factors affecting the efficiency of the performance management system in public service institutions – suitability of using standard models of performance management, role of social responsibility in the performance management and interconnection of organizational and individual performance objectives in public service institutions